2016
DOI: 10.5815/ijisa.2016.07.08
|View full text |Cite
|
Sign up to set email alerts
|

Review, Design, Optimization and Stability Analysis of Fractional-Order PID Controller

Abstract: This paper will establish the importance and significance of studying the fractional-order control of nonlinear dynamical systems. The foundation and the sources related to this research scope is going to be set. Then, the paper incorporates a brief overview on how this study is performed and p resent the organization of this study. The present work investigates the effectiveness of the physical-fractional and biological-genetic operators to develop an Optimal Form of Fract ional-order PID Controller (O2Fo-PID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 66 publications
(78 reference statements)
0
22
0
Order By: Relevance
“…The gain matrix K can be obtained using equation (14). (14) where the matrix P is derived from Riccati equation according to equation (15).…”
Section: B Lqr Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gain matrix K can be obtained using equation (14). (14) where the matrix P is derived from Riccati equation according to equation (15).…”
Section: B Lqr Methodsmentioning
confidence: 99%
“…Some researchers have tried to apply different types of flight control methods to an aircraft, in particular, the quadrotor series. They consist of PID (Proportional, Integral and Derivative) methods [14] [15], LQ (Linear Quadratic) [16] [17] [18], utilising fusion and filter methods such as complementary methods, DCM (Direct Cosine Matrix) filters, and the Kalman filter method [19]. LQ methods, such as LQR (Linear Quadratic Regulator) and LQG (Linear Quadratic Gaussian) utilising HJB (Hamilton-Jacobi-Bellman) equations in managing cost functions to achieve optimal control.…”
Section: Introductionmentioning
confidence: 99%
“…Autotuning methods for fractional order PID controllers were also proposed [21][22][23]. Some rather recent review papers on fractional order controllers can be found in [24][25][26] and provide an insight into fractional order control of different types. An excellent review paper on fractional order controllers, including their most widely used continuous and discrete approximation methods, as well as their digital and analogue implementation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Integer order system control by posing it as a fractional order system has been proposed in [38], wherein parameter  acts as input to the fuzzy controller, and µ as output. A review of physicalfractional and biological-genetic operators for modeling and control of industrial process by using multi objective genetic algorithm to optimize the parameters of the FOPID is analyzed in [39]. In [40], authors have presented fractional-order feedback controller for control and synchronization of fractional-order chaotic systems.…”
Section: Introductionmentioning
confidence: 99%